Genetic diversity of the class II major histocompatibility DRA locus in European, Asiatic and African domestic donkeys - Vranova, Marie; Alloggio, Ingrid; Qablan, Moneeb; Vyskocil, Mirko; Baumeisterova, Aneta; Sloboda, Michal; Putnova, Lenka; Vrtkova, Irena; Modry, David; Horin, Petr (Infection, genetics and evolution, 2011)
The major histocompatibility complex (MHC) genes coding for antigen presenting molecules are the most polymorphic genes in vertebrate genome. The MHC class II DRA gene shows only small variation in many mammalian species, but it exhibits relatively high level of polymorphism in Equidae, especially in donkeys. This extraordinary degree of polymorphism together with signatures of selection in specific amino acids sites makes the donkey DRA gene a suitable model for population diversity studies. The objective of this study was to investigate the DRA gene diversity in three different populations of donkeys under infectious pressure of protozoan parasites, Theileria equi and Babesia caballi. Three populations of domestic donkeys from Italy (N = 68), Jordan (N = 43), and Kenya (N = 78) were studied. A method of the donkey MHC DRA genotyping based on PCR-RFLP and sequencing was designed. In addition to the DRA gene, 12 polymorphic microsatellite loci were genotyped. The presence of Theileria equi and Babesia caballi parasites in peripheral blood was investigated by PCR. Allele and genotype frequencies, observed and expected heterozygosities and F(IS) values were computed as parameters of genetic diversity for all loci genotyped. Genetic distances between the three populations were estimated based on F(ST) values. Statistical associations between parasite infection and genetic polymorphisms were sought. Extensive DRA locus variation characteristic for Equids was found. The results showed differences between populations both in terms of numbers of alleles and their frequencies as well as variation in expected heterozygosity values. Based on comparisons with neutral microsatellite loci, population sub-structure characteristics and association analysis, convincing evidence of pathogen-driven selection at the population level was not provided. It seems that genetic diversity observed in the three populations reflects mostly effects of selective breeding and their different genetic origins.
Keywords: Demography; Microsatellite Repeats; Babesiosis; Asie; Genotype; zvířata; Europe; geny MHC třídy II; genetická variace; Africa; Genetic Variation; Afrika; babezióza; Genes, MHC Class II; mikrosatelitní repetice; demografie; Equidae; Asia; genotyp; Animals; Evropa